World Population Variability and Heat Bias Prediction: An Approach to Global Heat Disaster Management - Peace, Nwaerema; Liman, Hadiza Muhammad (International Journal of Climate Research, 2020)
This study examined world population variability and heat bias prediction as an approach to global heat disaster management. Heat bias data were generated from population records of United Nations Department of Economic and Social Affairs, World Population Review and U.S. Census Bureau and International Database using population simulated mathematical model. The world has population of 7,794,798,739 and heat bias of 7.20C and continental mean of 5.40C. Asia had the highest heat bias of 70C, Africa 6.0C, North America 6.40C, Europe 5.70C, South America 5.50C Australia/Oceania 4.80C and the Antarctica had the least heat bias of 2.20C ranging 4.80C. All continents exceeded the recommended +0.5oC-2.5oC human comfort threshold. Countries within the humid tropics had increased heat load. Countries within the subtropics up to the middle latitude had relatively lower heat stress. Population density does not have significant association with heat bias. Heat bias is important in global environmental planning and management.